Systemowe nauczanie literatury a integracyjne tendencje w nauce = Systemic Teaching of Literature and Interpretative Tendencies - Pasterniak, Wojciech (1935-2018) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In his paper the author cheeks on two competitive hypothesises: on the need of systematic teaching of literature and on the possibility of asystematic teaching. He establishes three general characteristics of systematic teaching: a) an optimum of organization of newly acquired experiences, b) connexion of newly acquired experiences with hitherto obtained, c) adoption of theoretical knowledge to practice
Keywords: dydaktyka literatury; integracja w nauce